ANALYSIS OF FACTORS AFFECTING THE SAVING BEHAVIOR OF WORKERS IN BATAM CITY - Jesclin Jesclin; Wisnu Suyono (Universitas Internasional Batam, 2022)
This study aimed to determine the factors that influence the saving behavior of workers in Batam City. Batam City has the second-highest cost of living in Indonesia. The high cost of living causes Batam City workers to find it difficult to set aside savings funds. The variables used in this study were a parental influence, peer influence, attitude toward saving, self-control, financial knowledge, and financial literacy. Data were obtained through a survey of 400 workers in Batam City and then analyzed using Smart PLS version 3.2. The results showed that parental influence, peer influence, attitude toward saving, financial knowledge, and financial literacy had a significant positive effect on saving behavior, financial knowledge had a significant positive effect on financial literacy, and financial knowledge had a significant effect on saving behavior with financial literacy as a mediating variable. In contrast, self-control has a non-significant effect on the saving behavior of workers in Batam City. The results of this study are hoped to be a consideration for financial institutions to plan and prepare strategies to encourage people to save.